Ultrasound Screening of Fetal Anomalies at 11–13+6 Weeks. Issue 3 (8th July 2020) - Ding, Wen-Ping; Li, Nan; Chen, Min
Abstract : Abstract: During the past decades, early fetal ultrasound and diagnosis have increasingly gained attention in pregnancy care with the development of high-frequency transducers, which make it possible to obtain detailed images of the early fetus and its organs, and thus move part of the anatomy and anomaly scan from the second to the first-trimester. By transabdominal sonography or transvaginal sonography, or a combination of both approaches, it is now able to diagnose a wide variety of fetal abnormalities at 11–13 +6 weeks.